FAKTOR KEPERILAKUAN DALAM IMPLEMENTASI PERATURAN PERUNDANG-UNDANGAN PENYUSUNAN DAN PENGELOLAAN KEUANGAN DAERAH (STUDI EMPIRIS PADA SATUAN KERJA PENGELOLA KEUANGAN DAERAH KABUPATEN LAMONGAN) - TRI SUTRISNO, ANDIK Tri (Jurnal Akuntansi AKUNESA, 2012)
This study examines empirically the impact of antecedent factors on managerial performance of local government in the implementation of regulation of the budget systems. This study aims to test the direct influence of factors such as the use of regulation of the budget system, attitude, anxieties, ease of use, and usefulness in improving managerial performance of local government.This study uses primary data from the respondents' answers to questions related to the impact of antecedent factors in the use of regulation of the budget systems on managerial performance of local government in Lamongan. This analysis is based on data from 128 respondents through the questionnaire research.Based on the results of data analysis and testing hypothetical, the conclusion can be drawn from antecedent factors tested, only ease of use does not have a significant positive influence in improving the managerial performance. Keywords: Use of Regulation of the budget systems, Attitude, Anxieties, Ease of Use, Usefulness, and Managerial Performance.